3D crosslinked and interlocked graphene nanointerface enables ultra-tough and strong alumina - Yameng Jiao; Caixiang Xiao; Qingliang Shen; Xuemin Yin; Shouyang Zhang; Wei Li; Chuanyun Wang; Hejun Li; Qiang Song (Journal of Materiomics)
The mechanics of structural ceramics, especially the toughness, are crucial to their service reliability and need to be continuously optimized. Inspired by the “brick-mortar” structure and further adjusting the microstructure of “mortar” on the interface, ceramic with strength and toughness up to 444.16 MPa and 13.79 MPa⋅m1/2 is constructed by hot pressed sintering with alumina (Al2O3) as brick and vertical graphene (VG) with active atomic edges as mortar. Relying on the covalent interface between VG grown in-situ and Al2O3, the sliding of Al2O3 links the shear-deformation process of the crosslinked and interlocked nanointerface formed by VG, making the VG-enhanced Al2O3 ceramics (AVG) obtain super toughness. Moreover, the structure of interlocked VG-nanointerface exhibits an excellent high-temperature resistance, which makes AVG still show the excellent strength of 437.66 MPa and toughness of 11.16 MPa⋅m1/2 after heat treatment at 1500 °C for 100 h and they are respective 2.51 times and 3.18 times higher than Al2O3 in the same condition. This work provides a new thought for the preparation of high-strength, ultra-tough and high-temperature mechanical stable ceramics.